Odpowiedzi

Najlepsza Odpowiedź!
2010-03-06T21:13:25+01:00
A)4*(-0,5)²+6*(-⅔)²=4*0,25+6*4/9=1+8/3=3 ⅔
b)(½)²+(-0,8):(-⅘)=¼+1=1¼
c)⅔+[(-⅓)²+(-⅓)²]:⅓=⅔+(1/9+1/9):⅓=⅔+2/9*3=⅔+⅔=1⅓
d) (4*3/(2²)-(2²)/5):2,2=(12/4-4/5):2,2=(3-0,8):2,2=2,2:2,2=1
2010-03-06T21:16:32+01:00
A)4*(-0,5)²+6*(-2/3)²=4*0,25+6*4/9=1+12/3=1+4=5
b)(1/2)²+(-0,8):(-4/5)=1/4-0,8:(-4,5)=1/4*1=1/4
c)2/3+[(-1/3)²+(-1/3²]:1/3= 2/3+(1/9-1/9):1/3=2/3+0: 1/3=2/3:1/3=2/3*3=2
d) (4*3/2²-2/5²):2,2 = (4*9/4-4/25):2,2=9-4/25:2,2=7 i 21/25:22/10=21/25*10/22=2/10=1/5

licze na maxa;)